2013
DOI: 10.1002/ejic.201201080
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complexes with Schiff Bases Containing a Disiloxane Unit: Synthesis, Structure, Bonding Features and Catalytic Activity for Aerobic Oxidation of Benzyl Alcohol

Abstract: Mononuclear copper(II) salen‐type Schiff base complexes, CuIIL1–5 [H2L1 to H2L5 = tetradentate N,N,O,O ligands derived from 2‐hydroxybenzaldehyde, 2,4‐dihydroxybenzaldehyde, 3,5‐dibromo‐2‐hydroxybenzaldehyde, 2‐hydroxy‐5‐nitrobenzaldehyde, 5‐chloro‐2‐hydroxybenzaldehyde and 1,3‐bis(3‐aminopropyl)tetramethyldisiloxane, respectively] were prepared in situ in the presence of a copper(II) salt or by direct complexation between a copper(II) salt and a presynthesised Schiff base. The compounds {CuL1, CuL1·0.5Py, CuL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 118 publications
2
42
1
Order By: Relevance
“…18,46,47 It was recently reported that copper(II) complexes of a terpyridine derived ligand catalyzed the aerobic oxidation of benzylic alcohols in aqueous basic media with up to 94% yield. 18,48 Initially, we performed the oxidation of benzylic alcohol by using copper complex (R)-1 as catalyst with a low load (0.25%) at room temperature and a 0.2 M of K 2 CO 3 solution in water as reaction media in the presence of TEMPO (5 mol%), by taking advantage of water as a green solvent. Pleasingly, 31% yield of the only product, benzaldehyde was detected after 22 h (entry 1, Table 1).…”
Section: Catalytic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…18,46,47 It was recently reported that copper(II) complexes of a terpyridine derived ligand catalyzed the aerobic oxidation of benzylic alcohols in aqueous basic media with up to 94% yield. 18,48 Initially, we performed the oxidation of benzylic alcohol by using copper complex (R)-1 as catalyst with a low load (0.25%) at room temperature and a 0.2 M of K 2 CO 3 solution in water as reaction media in the presence of TEMPO (5 mol%), by taking advantage of water as a green solvent. Pleasingly, 31% yield of the only product, benzaldehyde was detected after 22 h (entry 1, Table 1).…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…However, aliphatic or secondary benzylic alcohols were confirmed to be challenging substrates for oxidation under the optimized conditions (entries 17 and 18), as also found for other Cu II /TEMPO catalysts. 18,48 The complex (S,R)-2 was also examined for the oxidation of benzylic alcohols. It was noted that the oxidation of benzyl alcohol resulted in a 78% yield of benzaldehyde, in the presence of 0.5 mol% of (S,R)-2 under the same conditions (5 mol% TEMPO, 5 cm 3 of 0.2 M K 2 CO 3 in water, 70 ºC and 22 h), and the TON was much lower than that found for (R)-1 (156 vs. 770) (entry 19, Table 1).…”
Section: Catalytic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three metal complexes containing siloxane bond and manganese (M 1 L), iron (M 2 L), and chromium (M 3 L) in their structure, were used as fillers and have been prepared according to procedure reported in [19] and described in Supplementary Information Purolite CT-175, a styrene-divinylbenzene ion exchanger with -SO 3 H groups (4.1 mequiv./g) was dehydrated by azeotrope distillation with toluene and vacuumation at 110 °C/10 mm Hg before use.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Copper(II) complexes have been proved to possess excellent catalytic activity towards a number of organic reactions. [5][6][7][8] In particular, copper complexes derived from Schiff bases are amongst the most versatile catalysts known for oxygenation reactions. [9][10][11] The role played by copper ions in the active sites of a large number of metalloproteins has stimulated efforts to design and characterize copper complexes as models for a better understanding of biological systems.…”
Section: Introductionmentioning
confidence: 99%